ANALISIS TRANSFORMASI STRUKTUR EKONOMI PADA DAERAH OTONOM BARU - Rendy Alvaro; Ade Nurul Aida; Riza Aditya Syafri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
The aim of this research is to examine what sectors can be developed and have competitiveness, as well as determine changes in the economic structure of the new autonomous regions, including South Papua, Central Papua, Mountain Papua, and Southwest Papua. This research uses the LQ method and shift-share analysis. The results of sector mapping in 2010 and 2019 show that sectors are undergoing transformation, namely the Information and Communication sector, Education Services, Government Administration, Defense and Mandatory Social Security, other services, and the processing industry. Then the shift-share analysis shows that the processing industry and the Agriculture, Forestry, and Fisheries sectors do not have relatively good competitiveness when compared with the same sectors on a national scale. The results of the Klassen typology show that throughout the Papua region, the Government Administration, Defense, and Mandatory Social Security sectors are in Quadrant I. Meanwhile, the Accommodation and Food and Drink Provision sectors and Electricity and Gas Procurement throughout the Papua region are in Quadrant III. For this reason, apart from incentive support, policy support is needed from the central government and governments in DOB.